The Rare Case of a Probably True IgE-Mediated Allergy to Local Anaesthetics - Christina Fellinger; Felix Wantke; Wolfgang Hemmer; Gabriele Sesztak-Greinecker; Stefan Wöhrl (Case Reports in Medicine)
The majority of immediate type adverse reactions to local anaesthetics seem to be non-IgE-mediated. We report a case of a 31-year-old woman, who developed conjunctivitis and conjunctival erythema immediately after intrauterine application of a local anaesthetic. Skin prick testing and intradermal testing were done with lidocaine, mepivacaine, and procaine. Intradermal testing showed positive reactions to mepivacaine (1 : 10), undiluted lidocaine, and procaine (1 : 10 and undiluted). Specific IgE could be detected against mepivacaine, but not against latex. Serum tryptase was in the normal range. In order to rule out the exceptional case of a true IgE-mediated reaction, allergy testing with local anaesthetics is still required in the workup of patients.